Cadangan Airtanah Berdasarkan Geometri dan Konfigurasi Sistem Akuifer Cekungan Airtanah Yogyakarta-Sleman, Provinsi Daerah Istimewa Yogyakarta - , VICTOR ALELUIA DE SOUSA VICENTE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yogyakarta-Sleman Groundwater Basin covers territory of Sleman regency, City of Yogyakarta and Bantul Regency, which today have grown into dense residential areas. The excessive use of groundwater for domestic purposes, agriculture and industries would lead to degradation of the quality and quantity of groundwater. To overcome this problem, it is necessary to carry out a groundwater management which consists of various aspects, including evaluation of groundwater reserves and level of groundwater utilization in Yogyakarta-Sleman Groundwater Basin. The results of this work are expected to be used as a part of efforts to decide the proper step in groundwater management, in order to create effective and efficient use of groundwater in a sustainable manner. The purpose of this thesis is to obtain important data of Yogyakarta-Sleman Groundwater Basin which includes geometry and configuration of the aquifer system, static groundwater reserves, dynamic groundwater reserves, groundwater recharges, minimum distance between pumping wells, and groundwater use level. The research methodology is divided into several stages consisting of the preparation phase, collection of secondary data phase which is include data of hydrostratigraphy, hydroclimatology, transmissivity, storativity, hydraulic conductivity, and groundwater utilization, data analysis phase and report preparation phase. Based on the result of research, sub-district that has the largest number of static groundwater reserve is Pakem. The main factor that control this result is Pakem subdistrict has larger area compared to others sub-districts. Meanwhile, Ngemplak is the sub-district that has the largest amount of dynamic groundwater reserves. This result is controlled by the immense value of transmissivity in Ngemplak. Based on recharge evaluation, area that has the largest amount of groundwater recharge is located in Pakem Sub-district. The main factor that control this result is Pakem sub-district has larger area compared to others sub-districts. Meanwhile, Sub-districts with the largest minimum distance between pumping wells is Bambanglipuro. The main factors that control the outcome of this is the value of drawdown and transmissivity. The level of groundwater use in general is influenced by the geometry and configuration of the groundwater basin aquifer systems. Subdistricts that are on the edge of the groundwater basin groundwater utilization levels tend to have higher groundwater use than those who located in the central areas of the basin.